Faktor-Faktor Yang Mempengaruhi Anak SD Berbicara Kasar Dan Cara Mengatasinya - Rani Nur Hidayah; Eolalia Fadya Trisnawati; Eka Ratna Istari Putri; Arrozika Sabrina Apriliana; Sri Suwartini (Pusat Riset dan Inovasi Nasional, 2025)
The use of harsh or inappropriate language among elementary school children has become a concerning behavioral issue, as it can negatively impact their emotional and social development. This study aims to examine the underlying factors that contribute to children's use of offensive language, as well as to explore possible strategies for addressing this behavior. The contributing factors are classified into two main categories: internal and external. Internal factors include attention-seeking behavior, a desire for stimulation, and difficulties in emotional regulation. External factors involve influences from family upbringing, the residential environment, peer interactions, and cultural or social norms that tolerate the use of inappropriate language. This research employs a quantitative method with a document analysis approach to identify patterns and trends based on relevant literature. The findings indicate that both internal and external factors significantly influence children's tendency to use harsh language. Therefore, collaboration between parents, teachers, and the broader community is essential in providing guidance, positive examples, and continuous education to help children develop respectful and constructive communication habits.